In vivo tracing of the ascending vagal projections to the brain with manganese enhanced magnetic resonance imaging - Oleson, Steven; Cao, Jiayue; Wang, Xiaokai; Liu, Zhongming (Frontiers in neuroscience, 2023)
The vagus nerve, the primary neural pathway mediating brain-body interactions, plays an essential role in transmitting bodily signals to the brain. Despite its significance, our understanding of the detailed organization and functionality of vagal afferent projections remains incomplete.IntroductionThe vagus nerve, the primary neural pathway mediating brain-body interactions, plays an essential role in transmitting bodily signals to the brain. Despite its significance, our understanding of the detailed organization and functionality of vagal afferent projections remains incomplete.In this study, we utilized manganese-enhanced magnetic resonance imaging (MEMRI) as a non-invasive and in vivo method for tracing vagal nerve projections to the brainstem and assessing their functional dependence on cervical vagus nerve stimulation (VNS). Manganese chloride solution was injected into the nodose ganglion of rats, and T1-weighted MRI scans were performed at both 12 and 24 h after the injection.MethodsIn this study, we utilized manganese-enhanced magnetic resonance imaging (MEMRI) as a non-invasive and in vivo method for tracing vagal nerve projections to the brainstem and assessing their functional dependence on cervical vagus nerve stimulation (VNS). Manganese chloride solution was injected into the nodose ganglion of rats, and T1-weighted MRI scans were performed at both 12 and 24 h after the injection.Our findings reveal that vagal afferent neurons can uptake and transport manganese ions, serving as a surrogate for calcium ions, to the nucleus tractus solitarius (NTS) in the brainstem. In the absence of VNS, we observed significant contrast enhancements of around 19-24% in the NTS ipsilateral to the injection side. Application of VNS for 4 h further promoted nerve activity, leading to greater contrast enhancements of 40-43% in the NTS.ResultsOur findings reveal that vagal afferent neurons can uptake and transport manganese ions, serving as a surrogate for calcium ions, to the nucleus tractus solitarius (NTS) in the brainstem. In the absence of VNS, we observed significant contrast enhancements of around 19-24% in the NTS ipsilateral to the injection side. Application of VNS for 4 h further promoted nerve activity, leading to greater contrast enhancements of 40-43% in the NTS.These results demonstrate the potential of MEMRI for high-resolution, activity-dependent tracing of vagal afferents, providing a valuable tool for the structural and functional assessment of the vagus nerve and its influence on brain activity.DiscussionThese results demonstrate the potential of MEMRI for high-resolution, activity-dependent tracing of vagal afferents, providing a valuable tool for the structural and functional assessment of the vagus nerve and its influence on brain activity.